2017
DOI: 10.3329/bccj.v5i2.34388
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Dyslipidemia in different type of Myocardial Infarction

Abstract: Background: Dyslipidemia is one of the main risk factors with prognostic significance in relation to coronary heart disease. Aggressive treatment has been recommended in acute coronary syndrome (ACS). We examined pattern of dyslipidemia in ST Elevation myocardial infarction (STEMI) and Non- ST elevation myocardial infarction (NSTEMI). We also compare the lipid status in between two types of myocardial infarction (MI).Methods: This cross sectional observational study was carried out enrolling 100 subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Similar sex ratio with male predominance were also observed by other studies. [10][11][12] Regarding the traditional risk factors, it was found in the current study that, most of the patients of AMI (211/224; 94.2%) had unrecognized dyslipidemia. Similar to this finding reported such high prevalence (85.1% and 82.1% respectively) of unrecognized dyslipidemia among the admitted patients for first time AMI.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Similar sex ratio with male predominance were also observed by other studies. [10][11][12] Regarding the traditional risk factors, it was found in the current study that, most of the patients of AMI (211/224; 94.2%) had unrecognized dyslipidemia. Similar to this finding reported such high prevalence (85.1% and 82.1% respectively) of unrecognized dyslipidemia among the admitted patients for first time AMI.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies from Bangladesh reported similar age distribution of patients with AMI with mean age around 51 years with maximum number of the patients in the age range of 51-60 years. [10][11][12] In contrast to these findings from Bangladesh, studies from India reported comparatively higher mean age like 62.74 ± 13.6 years, 13 56.06 ± 11.29 years,14 and 56.75 ± 10.47 years. 15 Moreover, western study has reported higher mean age as compared to these studies conducted in Asia such as study (68 years).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations